2010
DOI: 10.1093/carcin/bgq270
|View full text |Cite
|
Sign up to set email alerts
|

Mthfd1 is a modifier of chemically induced intestinal carcinogenesis

Abstract: The causal metabolic pathways underlying associations between folate and risk for colorectal cancer (CRC) have yet to be established. Folate-mediated one-carbon metabolism is required for the de novo synthesis of purines, thymidylate and methionine. Methionine is converted to S-adenosylmethionine (AdoMet), the major one-carbon donor for cellular methylation reactions. Impairments in folate metabolism can modify DNA synthesis, genomic stability and gene expression, characteristics associated with tumorigenesis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 42 publications
2
28
1
Order By: Relevance
“…Consistent with these findings, previous studies of the Mthfd1 gt/+ mouse model showed that a 50% reduction in MTHFD1 protein led to reduced hepatic S-adenosylmethionine levels (21), lower methylation potential (19), elevated plasma homocysteine (22), and lower levels of methionine (23), indicating impaired function of the homocysteine remethylation cycle. However, the proband exhibited relatively mild elevations in plasma homocysteine concurrent with lower serum methionine and elevated homocysteine (8).…”
Section: Discussionsupporting
confidence: 79%
“…Consistent with these findings, previous studies of the Mthfd1 gt/+ mouse model showed that a 50% reduction in MTHFD1 protein led to reduced hepatic S-adenosylmethionine levels (21), lower methylation potential (19), elevated plasma homocysteine (22), and lower levels of methionine (23), indicating impaired function of the homocysteine remethylation cycle. However, the proband exhibited relatively mild elevations in plasma homocysteine concurrent with lower serum methionine and elevated homocysteine (8).…”
Section: Discussionsupporting
confidence: 79%
“…Surprisingly, Mthfd1 gt/Ï© animals do not develop neural tube defects even when fed a folate-deficient diet (28) and exhibit decreased levels of uracil in nuclear DNA in both liver (Table 3) and colon (23). The decrease in uracil in DNA is not explained by increased thymidylate salvage pathway activity as thymidine kinase 1 is not up-regulated in Mthfd1 gt/Ï© liver (Fig.…”
Section: Discussionmentioning
confidence: 88%
“…gt/Ï© mice accumulate less uracil in colon genomic DNA as compared with Mthfd1 Ï©/Ï© littermates (23). Here it is shown that Mthfd1 gt/Ï© liver DNA is also resistant to uracil accumulation Values are represented as the mean Ïź S.D.…”
Section: Mthfd1 Gt/Ï© Mice Are Protected From Uracil Misincorporation mentioning
confidence: 92%
“…DHF reductase (DHFR) reduces DHF to THF. 5,10-methyleneTHF can be regenerated either from serine and THF through the activity of serine hydroxymethyltransferase (SHMT1 or SHMT2α) or from formate, ATP, NADPH, and THF by the activity of methylenetetrahydrofolate dehydrogenase 1 (MTHFD1) (4)(5)(6). SHMT1, DHFR, and TYMS are small ubiquitin-like modifier (SUMO)-ylated and translocate to the nucleus at the G1/S boundary (7)(8)(9)(10)(11)(12)(13)(14)(15)(16).…”
mentioning
confidence: 99%